Effect of age on the incidence of aseptic meningitis following immunization with monovalent mumps vaccine. Issue 45 (9th November 2015) - Muta, Hiromi; Nagai, Takao; Ito, Yuhei; Ihara, Toshiaki; Nakayama, Tetsuo
Abstract: Objective: The purpose of this study was to determine the risk of aseptic meningitis after mumps vaccination in younger children compared with older children. Methods: This prospective cohort study included a total of 21, 465 children under 18 years of age who had received the first dose of three of the Japanese mumps monovalent vaccine. We compared the cumulative incidence of aseptic meningitis for 30 days after vaccination among the following age groups: ≤1, 2, 3–4, and ≥5 years old. We also investigated the cumulative incidence of salivary gland swelling, a fever (≥38 °C) lasting at least 3 days during the 10 to 25 days following immunization, vomiting of 3 times or more, headache, and seizure. Results: A total of 10 aseptic meningitis, 551 salivary gland swelling, 844 fevers, 669 vomiting, 757 headaches, and 29 seizure cases were identified. The cumulative incidence of aseptic meningitis increased with age (0.016%, 0.021%, 0.066%, and 0.096%, respectively). Statistical significance was observed between children ≥3 years old and those <3 years of age [0.078% vs. 0.018%, RR 4.35 (95% CI 1.05–18.2), p  = 0.04]. The cumulative incidence of salivary gland swelling also increased with age (1.8%, 3.0%, 3.5%, and 4.5%, respectively). For non-specific adverse events, the cumulative incidence of fever or seizure decreased with age. In contrast, the cumulative incidence of headache increased with age. The cumulative incidence of vomiting was similar among children ≤4 years of age; however, that in those children ≥5 years old was significantly lower. Conclusions: The first dose of mumps vaccine that is currently available for use in Japan may be administered in children less than 3 years of age in order to complicate a less aseptic meningitis after immunization.